FORMATION OF CLOSED REVOLUTION SURFACE MICRORELIEF UNDER CONDITIONS OF KINEMATIC INSTABILITY OF CUTTING PROCESS AT NUMERICALLY AND PROGRAM CONTROLLED MACHINE TOOLS - I. A. Kashtalyan (Наука и техника)
The paper considers peculiar features concerning a microrelief formation of grooves, turnings and chutes while executing «in widening» machining at numerically and program controlled machine tools. Some results of the experimental research are presented in the paper.